The Role Of Life Cycle Sustainable Assessment (Lcsa) In Achieving Sustainable Palm Oil Production: A Metaanalysis - Najat Omran, Amir Hamzah Sharaai , Ahmad Hariza Bin Hashim , Mohd Mansor Ismail (International Journal of Advanced Science and Technology, 2020)
Palm oil industry is an important source of economic growth and social development in the producer countries. Nevertheless, it has been facing some negative reports that may affect the industry’s sustainability. In order to ensure the continuance of this industry, comprehensive and easily understandable sustainability assessment-tools are needed. Current approaches based on methods like Life Cycle Assessments or Multi-Criteria-Decision-Analysis (MCDA) have weaknesses in terms of comprehensiveness, processing of uncertainty and subjectivity, and visualization of results. Thus, this paper highlighted the importance of establishing a life cycle sustainability assessment (LCSA) method to assess the sustainability of the product as well as itsapplication and challenges of use. This comprehensive review observed that there are needs to harmonizethe three life cycle methods within LCSA and improve the communication techniques for results interpretation. Moreover, the recommendations about the conducting of LCSA is desirable and the application of LCSA in case studies are required as well. Therefore, the finding from this comprehensive review could be help researchers and  practitioners as it outlines the application and existing limitation for assessing the sustainability of the product using the three life cycle methods within LCSA.